(untitled) (Global Journal of Medical Research, 2017)
Disease of the paranasal sinuses (PNS) is a global public health problem, with the only treatment option available being endoscopic surgery. Previous studies have suggested that anatomical variations of the PNS are common in different populations; however, there is little information available to verify this. Hence, the objective of the present study was to determine the prevalence of different anatomical variations of the PNS and nasal cavity among Sudanese patients who were referred by ear, nose and throat (ENT) surgeons for a computed tomography (CT)-aided study. The total number of patients eligible for the study was 557; of these, 51 were excluded, 317were in the study group, and 189 were controls. The CT images were carefully reviewed and discussed with the involvement of consultant radiologists, an anatomist, and an otolaryngologist. Our results showed that there was extensive pneumatization of the frontal sinus (FS) in 37% of cases, a rudimentary FS in 11%, and absence of the FS in 12%. In addition, the Keros classification showed the FS to be normal in 55%, type I in 27%, type IIin 10%, type III in 6%, and type IV in only 2% of patients. A large ethmoid bulla (EB) was found in 43% of patients, but the remaining 57% had a normal ethmoid sinus.